My dog may be a genius : poems - Prelutsky, Jack (Greenwillow Books, 2008)
Have you ever encountered an underwater marching band, a pig in a bathing suit, a pet orangutan, or a witch in a hardware store? Have you ever sat with a skunk in a courtroom, shopped for a dinosaur, or conversed with a Bupple, a Wosstrus, a Violinnet, or a Celloon? You will have, once you've read collection of poems.